A Grounded Theory of Moral Reckoning in Nursing - Alvita Nathaniel (Grounded Theory Review: An International Journal, 2004)
Moral distress is a pervasive problem in nursing, contributing to nurses’ emotional and physical health problems, loss of nurses’ ethical integrity, dissatisfaction with the work of nursing, and loss of nurses from the workforce. The purpose of this research was twofold: 1) to further elucidate the experiences and consequences of professional nurses’ moral distress and 2) to formulate a logical, systematic, and explanatory theory of moral distress and its consequences. METHOD: This Glaserian grounded theory study utilized volunteer and purposive sampling to recruit 21 registered nurses. Analysis of the data resulted in an original substantive theory of moral reckoning in nursing, which reaches further than the concept of moral distress, identifying a critical juncture in nurses’ lives and better explaining a process that affects nurses and the health care that they deliver. Results: Moral reckoning in nursing consists of a three-stage process. After a novice period, the nurse experiences a Stage of Ease in which there is comfort in the workplace and congruence of internal and external values. Unexpectedly, a situational bind occurs in which the nurse’s core beliefs come into irreconcilable conflict with social norms. This forces the nurse out of the Stage of Ease into the Stage of Resolution, in which the nurse either gives up or makes a stand. The nurse then moves into the Stage of Reflection in which beliefs, values, and actions are iteratively examined. The nurse tries to make sense of experiences through remembering, telling the story, examining conflicts, and living with the consequences. Implications: In today’s complex health care system, nurses find themselves faced with morally troubling situations which if not resolved can lead to serious consequences for nurses, patients, and the health care system as a whole. This study sets the stage for further investigation on the human consequences of moral distress. Further, since moral reckoning impacts health, nurse leaders are challenged to identify opportunities to facilitate successful moral reckoning in the workplace through encouraging nurses to tell their stories, examine conflicts, and participate as partners in moral decision making.